PENGARUH STRATEGI PEMASARAN DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PENGGUNA JASA KURSI PIJAT DI PT. NUSANTARA SEHAT-PERFECT RELAXIN BANDARA DEPATI AMIR KOTA PANGKALPINANG - Angraini, Suci; Reniati, Reniati; Saputra, Darman (Faculty of economcs Universitas Singaperbangsa Karawang, 2023)
This study aims to determine whether there is influence of marketing strategy and service quality on customer satisfaction. The population in this study were all massage chair service users at PT Nusantara Sehat-Perfect Relaxat Depati Amir Airport, Pangkalpinang City with sampling method nonprobability sampling by using incidental sampling method. The data analysis technique used is validity and reliability test, classic assumption test, multiple linear regression analysis test, t test, f test, and R test2by using Statistics Package for Social Science(SPSS) version 24. Based on the results of descriptive analysis on marketing strategy variables with a mean value of 3.37 (moderate), service quality of 3.35 (moderate), and consumer satisfaction of 3.34 (moderate). The results of this study indicate that the marketing strategy variable (X1) gets a value of tcount> ttable(6,161> 1.973), service quality variable (X2) gets the value of tcount> ttable (7.764 > 1.973). This means that marketing strategy, service quality, partially has a positive and significant effect on customer satisfaction. It is known from the F test that the significance value is less than 0.05 which is equal to 0.000, this shows that marketing strategy and service quality simultaneously have an influence and are significant on customer satisfaction. Based on the t test, it is known that partially marketing strategy and service quality simultaneously and significantly affect customer satisfaction.